Augmented Reality to Improve English Comprehension and Retention in Third-Grade Students - Apriyanto, Sigit; Apriadi, Eko Aziz; Anum, Adelina; Bahari, Arum (Journal Corner of Education, Linguistics, and Literature, 2025)
English proficiency at the elementary level in Indonesia remains relatively low, particularly in the Kalianda region of South Lampung, Sumatra. This issue has become a pressing concern ahead of the mandatory English policy for elementary schools starting in the 2027/2028 academic year. Indonesia’s score in the 2024 EF English Proficiency Index, ranked 80th out of 116 countries, underscores the urgency of renewing teaching methods. Currently, conventional approaches such as lectures and rote memorization dominate, while technology-based methods, including Augmented Reality (AR), are scarcely implemented at the primary education level, especially in Kalianda. The primary objective of this study is to develop and implement AR-based learning media to enhance the comprehension and retention of English materials among third-grade elementary students in Kalianda, South Lampung. The study employs a Research and Development (RnD) approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects comprised 134 third-grade students from five elementary schools in Kalianda, selected through cluster sampling. The AR application is developed by considering the distribution of basic English materials and an age-appropriate user experience for elementary students. Findings indicate that AR enhances comprehension and retention by providing interactive, multi-sensory experiences that support differentiated learning. Low-performing students achieved substantial improvements, while higher-performing students advanced further. No declines in scores were observed, highlighting AR’s effectiveness in creating an engaging, safe, and motivating learning environment that fosters meaningful, long-term learning outcomes.